Measurement of evidence conflict based on correlation coefficient - Ya-fei SONG; Xiao-dan WANG; Lei LEI; Ai-jun XUE (Tongxin xuebao)
In order to measure the conflict degree much better, criteria for correlation coefficient was defined based on analysis on the relation between evidence similarity and conflict. Then a new measurement of conflict was presented based on the definition of correlation coefficient. Theoretic proof and numerical examples verify the efficiency of the proposed measurement. It's illustrated that higher correlation coefficient indicates lower conflict degree between two bodies, and vice versa. Moreover, it has been shown by comparison with other methods that the proposed measurement is more comprehensive and reasonable than other measurements.